iHealth : a web portal for healthcare services - Kan, Kah Seng (Nanyang Technological University, 2020)
The Joint NTU-UBC Research Centre of Excellence in Active Living for the Elderly (LILY) is a world-class research centre is researching on frailty [1]. Frailty is a common syndrome found in the elderlies on getting weak that leads to increase risk for poor health. Researchers of LILY found solutions and proposed an end-to-end System for Assessment and Intervention of Frailty (SAIF) that will help to reduce the risk and slow down the progress of physical frailty. This includes creating intervention games catered to the elderlies for rehabilitation as well as grip and weight management which can detect and reduce frailty rate of the elderly. In order to view the data, users have to login to each individual applications or games to retrieve the results. This individual portal tends to vary from one another which is time consuming for users to get adapted to each individual user interface. In order to let the doctors, nurse, family members and caregivers of the elderly to easily access the frailty assessment, this project aims to develop an integrated frailty web portal called iHealth, which will allow them to view the detailed assessment of the elderly for all the games as well as assessment’s applications result. As the database is integrated with all games and assessment’s applications data, they share the same login credentials which enables the portal to show all the necessary information to the users. Family members of the elderly will be notified via browser notification for the latest activities they are attending.